PERTAHANAN NEGARA, REALITAS SOSIAL KEAGAMAAN, DAN ANCAMAN NONMILITER DI YOGYAKARTA* - Edy Santosa; Moh Soehadha; Heri Supriyanto (Asketik : Jurnal Agama dan Perubahan Sosial, 2021)
The concept and strategy of national security of Indonesia includes the resilience of all areas of thecountry against military and non-military threats. From a sociological perspective, non-militarythreats exist in a dynamic social and environmental world and are constantly changing in form.Non-military threats have a broader dimension, including ideological, social, economic, cultural,political, information technology and public safety. Various facts about regional conditions andsocio-religious dynamics in the Special Region of Yogyakarta are indicators that show a source ofproblems as a potential non-military threat. The article from the field research using the followingqualitative method contains an interpretive description of various non-military threats frominternal conditions, as well as external influences. Internal conditions are caused by the Yogyakartaregion which is directly adjacent to the Indian Ocean, the ring of fire area, and the city of studyand tourism destinations. As for the external conditions for non-military threats, among others,due to the influence of globalization, geopololitical conditions, ideological flows such as radicalismand massive caiptalization from outside Indonesia. There are three forms of non-military threatsin Yogyakarta that urgently need a strategy to respond and resolve them. The three non-militarytherats are religious radicalism, narcotics and illegal drugs, as well as the negative impact of virtualculture; such as the rise of hate and hoaxes that can damage unity, because it causes discord of thenation.